ANALYSIS OF THE EFFECT OF GREEN PERCEIVED RISK, GREEN PACKAGING, AND GREEN PRODUCT ON GREEN PURCHASE INTENTION ON CULINARY OR FOOD MSME PRODUCTS (STUDY ON STUDENT CONSUMERS IN SEMARANG CITY) - Hasanudin, Mohamad; Marliyati, Marliyati; Gayatrie, Christina Retno; Sulistyo, Sulistyo; Widiarto, Ardian (Politeknik Negeri Semarang, 2024)
After experiencing the Covid-19 Pandemic starting in 2023, the Indonesian economy began to rise but has not fully reached normal conditions. The same condition is also experienced by the MSME sector, especially the culinary / food sector. The impact of the economic recovery after the covid pandemic also has an impact on the increasing amount of waste. According to the Semarang City Environmental Agency (DLH), during the pandemic waste production started at 900 tons, even down to 650 tons, but now in 2022 after the covid pandemic began to end the amount of waste began to rise to 1200 tons of waste per day. This study aims to determine and analyze whether or not there is a relationship between the green economy perception variable which consists of: Green Perceived Risk Green Packaging and Green Product on Green Purchase Intention among students in Semarang city related to the implementation of Semarang mayor regulation no.27 of 2019 concerning plastic waste control in Semarang city. Data collection was carried out using a questionnaire or questionnaire method and observation. The data analysis method used in this research is Structural Equation Modeling with the Partial Least Square (SEM-PLS) algorithm approach. Based on the results of this study, it will be concluded that the effect value of Green Perceived Risk (X1) on Green Purchase Intention (Y) is a negative and insignificant effect on the attitude of desire to buy green products, thus H1 is rejected. The effect value of Green Packaging (X2) on Green Purchase Intention (Y) is a positive and insignificant effect on the interest in buying green products, thus H2 is rejected. The value of the influence of Green Product (X3) on Green Purchase Intention (Y) is a positive and significant effect on the interest in buying green products, thus H3 is accepted.